2012
DOI: 10.1200/jco.2012.30.15_suppl.6553
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of bendamustine plus rituximab versus CHOP-R in treatment-naive patients with mantle cell (MCL) and indolent lymphomas (IL).

Abstract: 6553 Background: To assess the cost-effectiveness of bendamustine plus rituximab (B-R) vs cyclophosphamide, doxorubicin, vincristine, prednisone, and rituximab (CHOP‑R) for treatment-naive patients with MCL or IL from a US healthcare payer perspective. Methods: A discrete event simulation was developed for a mixed population of patients with MCL or IL. Two arms were simulated, each containing 1000 identical MCL or IL patients treated with B-R or CHOP-R. Input data for baseline characteristics, overall respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…One cost-effectiveness Markov model analysis by Sabater et al found higher treatment and administrative costs with the use of BR compared to R-CHOP during induction, but overall cost savings with BR at 25 years, owing to better disease control. 22 Similar findings have been described by other groups, 23,24 suggesting BR is an overall costeffective regimen.…”
Section: Discussionsupporting
confidence: 84%
“…One cost-effectiveness Markov model analysis by Sabater et al found higher treatment and administrative costs with the use of BR compared to R-CHOP during induction, but overall cost savings with BR at 25 years, owing to better disease control. 22 Similar findings have been described by other groups, 23,24 suggesting BR is an overall costeffective regimen.…”
Section: Discussionsupporting
confidence: 84%
“…This study is the first evaluation focused on FL which assessed lifetime efficiency of R-B first-line strategy considering a rituximab maintenance for 2 years, as well as up to 2 potential relapses. Taking into account management of relapses rises as the key driver that explains the higher total costs in comparison of other economical evaluation [20,28,29] , and the long-term savings associated with R-B arm.…”
Section: Discussionmentioning
confidence: 99%